TECHNICAL DESIGN OF WATER INFRASTRUCTURE FOR MINI HYDRO ELECTRICAL POWER GENERATION (MHEP) PEKATAN ON WEST LOMBOK, NTB. - Intamani, Amigia
This paper discuss a study of stream flow utilization as an alternative energy resources for mini hydro electrical power generation (MHEP). Case study taken in this analysis is carried out at Segare river basin, locate in Pekatan, Tanjung Sub District, West Lombok District, NTB Province. It is expected that the construction of Mini Hydro Electrical Power Generation (MHEP) can be implemented by PLN to obtain Power installed capacity about 683 kW by utilizing Segare stream flow. Weir structure dimension is determined from flood hydrograph of Segare stream flow base on maximum daily rainfall by applying frequency analysis according to Gumbel distribution, while flood discharge for 50 years return period, some value of Q = 348 m3/sec is calculated by using SSARR model. Design discharge of Q = 5,23 m3/sec is obtained from optimization study refer to flow duration curve with consider several factors, namely; Power capacity, MHEP scheme, Head, Turbine operational and The low cost of Civil work and Electro- Mechanical equipments. The utilization of Segare river basin may give the other benefit beside MHEP development; i.e, irrigation for agriculture and water supply for domestic water use.